Napsin A-specific T-cell clonotypes are associated with improved clinical outcomes in patients receiving checkpoint immunotherapy for metastatic non-small cell lung cancer - Crystal Mackall; Heather Wakelee; Sylvia Lee; Keith D Eaton; Cristina Rodriguez; Rafael Santana-Davila; Joel W Neal; Natalie J Miller; Elena Sotillo; Tatyana Pisarenko; Eric Q Konnick; Christina Baik; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Background Napsin A is normally expressed in human lung pneumocytes and is a highly expressed cancer antigen in lung adenocarcinoma. We examined whether T cells specific for Napsin A may play a role in immune checkpoint inhibitor (ICI)-mediated responses. We used bulk T-cell receptor (TCR) repertoire data to assess whether the presence of Napsin A-specific clonotypes in the peripheral blood was associated with improved clinical responses to ICI.Methods Patients with metastatic non-small cell lung cancer (NSCLC) receiving anti-programmed cell death protein 1 (PD-1) and/or programmed death-ligand 1 (PD-L1) were enrolled at Fred Hutchinson Cancer Center and Stanford University Medical Center (n=62; histology of adenocarcinoma n=48, squamous n=9, NSCLC/other n=5). Peripheral blood mononuclear cells were collected for genomic DNA isolation at one pretreatment and one post-treatment time point (range 3 weeks to 3 months). TCRβ was bulk sequenced via the immunoSEQ platform (Adaptive Biotechnologies). Napsin A-specific TCRβ sequences were identified from publicly available data and their frequencies were quantified in each patient sample. We examined whether overall survival (OS) and progression-free survival (PFS) outcomes differed in patients with or without detectable Napsin A-specific TCRs (herein Napsin TCRs). We used Cox proportional hazards regression to assess the association between detectable Napsin TCRs and PFS or OS in univariable and multivariable analyses.Results Napsin TCRs were detectable in the blood in a large fraction of our cohort (n=25/62 (40%) pretreatment; n=21/42 (50%) post-treatment). Patients with detectable Napsin TCRs had a significant improvement in OS compared with patients without these TCRs (median OS 45.4 vs 14.8 months, p=0.0043 pretreatment; median OS 55.4 vs 18.9 months, p=0.0066 post-treatment). Among 27 HLA-A*02 carriers of 55 human leukocyte antigen-typed patients (49%), patients with detectable pretreatment Napsin TCRs had a significant improvement in OS (median 60.2 vs 16.5 months, p=0.0054) and PFS (median 21.5 vs 7.2 months, p=0.031) compared with patients without these TCRs. In univariate and multivariate analysis, the presence of Napsin TCRs pretreatment was associated with improved OS (p=0.0057, HR 0.40, 95% CI 0.21 to 0.76 univariate; p=0.033, HR 0.45, 95% CI 0.23 to 0.91 multivariate).Conclusions Napsin TCRs are frequently detected in patients with NSCLC and are associated with improved OS in patients with NSCLC receiving ICI.